Farmer Technical Knowledge of Reproductive Technology and Training Interventions - Tanri Giling Rasyid; Muhammad Darwis; Andi Suarda (International Journal of Agriculture System, 2019)
This study contributes to the improvement of knowledge of farmers based on reproductive technology training interventions in terms of knowing that signs of lust, how to administer hormones to cause uniformity of lust or estrus or prostaglandin, and to know the exterior shape of productive female beef cattle. This study uses a pre-test and post-test model approach through training interventions. Also using mixed method research is a methodology that combines qualitative and quantitative methods. This method allows researchers to present qualitative studies through descriptive explanations and also quantitatively through numbers, tables, graphs, charts and statistical data. For the measurement scale to quantify qualitative data, the measurement scale is Likert 3 levels. The results show that training interventions can improve the knowledge or skills and expertise of beef cattle farmers in terms of reproductive technology and minimize the dependence of farmers on extension workers.